2017
DOI: 10.5194/acp-17-13999-2017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of climate model aerosol seasonal and spatial variability over Africa using AERONET

Abstract: Abstract. The sensitivity of climate models to the characterization of African aerosol particles is poorly understood. Africa is a major source of dust and biomass burning aerosols and this represents an important research gap in understanding the impact of aerosols on radiative forcing of the climate system. Here we evaluate the current representation of aerosol particles in the Conformal Cubic Atmospheric Model (CCAM) with ground-based remote retrievals across Africa, and additionally provide an analysis of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 89 publications
(126 reference statements)
0
21
0
Order By: Relevance
“…The underestimation of CO columns exceeds the interannual variation in MOPITT observations, a feature that was also seen in other studies that used different atmospheric transport models and previous versions of the GFED data (Edwards et al, ; van Leeuwen et al, ). Additionally, the models driven by GFED cannot reproduce the late peak of satellite retrievals of NH 3 columns (Paulot et al, ) and aerosol optical depth (AOD; Horowitz et al, ; Magi et al, ; Tummon et al, ) over Africa. These tracers follow different chemical processes than CO and have shorter atmospheric lifetimes; therefore, the modeling biases are probably caused by the underestimated emissions of GFED in the late season rather than by modeling deficiencies.…”
Section: Annual Patterns and Seasonal Variations Of African Fire Co Ementioning
confidence: 99%
“…The underestimation of CO columns exceeds the interannual variation in MOPITT observations, a feature that was also seen in other studies that used different atmospheric transport models and previous versions of the GFED data (Edwards et al, ; van Leeuwen et al, ). Additionally, the models driven by GFED cannot reproduce the late peak of satellite retrievals of NH 3 columns (Paulot et al, ) and aerosol optical depth (AOD; Horowitz et al, ; Magi et al, ; Tummon et al, ) over Africa. These tracers follow different chemical processes than CO and have shorter atmospheric lifetimes; therefore, the modeling biases are probably caused by the underestimated emissions of GFED in the late season rather than by modeling deficiencies.…”
Section: Annual Patterns and Seasonal Variations Of African Fire Co Ementioning
confidence: 99%
“…9). Horowitz et al (2017) have suggested that biomass burning aerosol could make up a large fraction of the AOD in SWA during the burning season (December-February) from observations recorded in northern Benin (Djougou) and Nigeria (Ilorin). However, the coastal urban zone of SWA clearly lacks dedicated observations, which can in turn be used to understand local PM 2.5 variations better.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed AOD is an indicator of the aerosol load in the atmospheric column and its spectral behaviour provides information on the shape of the aerosol size distribution (O'Neill et al, 2003) and so the aerosol type. The AOD in the Sahel region has been largely investigated (Horowitz et al, 2017;Léon et al, 2009;Mallet et al, 2008) thanks to the availability of the AERONET automatic sun photometer (Holben et al, 1998). Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Observational data for a March period based on available data are reported in the literature [92], unfortunately the exact data are not available: observed values are averaged from available data, but a first estimate shows that CHIMERE for March 2014 produces the same order of magnitude for dust concentrations, the main hot spots in Cape Verde (16. [94], and also identified in the Conformal Cubic Atmospheric Model (CCAM) [95] where the dust lifetime is longer than the ones calculated in previous modeling exercises.…”
Section: Overview Of Pm Concentrations Simulated By Chimere Over the mentioning
confidence: 86%